The Influence of Complex Doping on Kinetics of Decomposition and Thermal Stability of Mg-Based Mechanical Alloys - Ershova, O.G.; Dobrovolsky, V.D.; Solonin , Yu.M. (Physics and Chemistry of Solid State, 2019)
Mechanical alloys (MАs) were synthesized by the method of reactive mechanical alloying. At a hydrogen pressure of 0.1 MPa, with the use of thermal desorption spectroscopy, the thermal stability, the kinetics of hydrogen desorption from the hydride phase MgH2 of the obtained MAs were studied. It has been established that the complex doping by of Fe, Si, Ti, leads to a significant improvement in the of hydrogen desorption from the hydride phase MgH2 of MA synthesized by the RMA. Hydrogen capacity CH of MА after reactive grinding for 20 h. was found to be equal to 5.7 % wt. Due to this alloying, the decrease in the thermodynamic stability of MgH2 is not established. The tested materials showed a high potential as hydrogen storage alloys especially for stationary application.